Kajian Peningkatan Kecekapan Tenaga Elektrik Untuk Pembangunan Komersial - Wan Chik, Mohd Faisal (Universiti Sains Malaysia, 2006)
Electric Energy Efficiency Enhancement of a Commercial Establishment is a research to evaluate several aspects that influencing efficiency of an electrical system. This project was done to investigate factors that contribute to inefficient electrical energy use, method to improve efficiency, and economic analysis effect to the electrical energy conservation. This project focused on 3 aspects that inherent as total load characteristic which consist air conditioning, indoor lighting and non linear load. Research that was done include the aspect of energy that is being used, power quality and savings methodology. For cooling load, two types of system was concern which is Air Cooled Package Unit and Air Cooled Split Unit to ensure either the system is efficient or not. For lighting system, the analysis involves to determine either the present systems operates at a cost effective value. For non-linear load, analysis that was done to determine either the rich harmonic current may affect the neutral sizing cable. Besides that, interactive and user friendly software was developed to analyze cost comparison between the capital cost, system operational cost and the investment payback. This report also consist some suggestion to enhance the electric energy efficiency, that is being discuss in a depth way.